A Dynamic Wind Generation Model for Power Systems Studies - Estanqueiro, Ana (2013)
In this paper, a wind park dynamic model is presented together with a base methodology for its application to power system studies. This detailed wind generation model addresses the wind turbine components and phenomena more relevant to characterize the power quality of a grid connected wind park, as well as the wind park response to the grid fast perturbations, e.g., low voltage ride through fault. The developed model was applied to the operating conditions of the selected sets of wind turbine experimental benchmark data from Azores and Alsvik wind parks, both for steady and transient operation of the grid. The results show a fairly good agreement in the relevant range of frequencies and indicate the model may be used as a tool for power system studies.